Comparative Analysis of Mean-Daily Value of Air Equivalent-Effective Temperature in Tbilisi and Kojori - Khazaradze, Ketevan R. (Journals of Georgian Geophysical Society, 2018)
For the confirmation of the applicability of the scale of air equivalent-effective temperature (EET) as the bioclimatic index in daily time scale, the results of studying the connection of average-daily values of EET in Tbilisi with the mortality of the population of this city from the cardiovascular diseases are represented. It is obtained that the dependence of mortality on EET takes the classical form - the decrease of mortality from the gradation "Sharply Coldly" to "Comfortably" with further increase to the gradation "Warmly". Thus, the existing scale EET is completely acceptable for the evaluation of the severity of exposure to the health of people on a daily scale also. The comparative analysis of mean-daily values of EET into Tbilisi (3 meteorological stations - Vashlijvari, Tbilisi state university, Tbilisi airport) and in Kojori (mountain health resort settlement in 10 km from the center of Tbilisi) is carried out. In particular it is shown that values of EET in the urbanized part of the city (Vashlijvari, State University) differ significantly from their values after the feature of city (Airport, Kojori); in Kojori are not observed negative for the health of people high values EET, which fall into the range by "Warmly".